Plant tissue culture : techniques and experiments - Park, Sunghun (Academic Press, 2021)
"Plant Tissue Culture: Techniques and Experiments, Fourth Edition, builds on the classroom tested, audience proven manual that has guided users through successful plant culturing for almost 30 years. The book's experiments demonstrate major concepts and can be conducted with a variety of plant materials readily available throughout the year. This fully updated edition describes the principles of the newest technologies, including CRISPR/Cas9 gene editing and RNAi technology with plant cell and tissue cultures and their applications. Bridging the gap between theory and practice, this book contains detailed methodology supported by comprehensive illustrations, giving users a diverse learning experience for both university students and plant scientists."--Provided by publisher